Analisis Kesalahan Berbahasa Putusan Pengadilan 111/Pdt.P/2022/PN.Pgp dalam Direktori Putusan Mahkamah Agung Sebagai Ancaman Kepastian Hukum - Aletha Naila Eva Eliana; Amanda Sofi Areta; Lucia Wulan Ratnawati; Putri Aulia Nur Jannah; Ferdy Adam Hanafi (VJJ, 2020)
The highest authority in the land relies on court rulings, which must be as precise as possible in language to provide rechtssicherheit, or legal certainty. But the truth is that even legitimate Indonesian items might have spelling or grammar mistakes. The purpose of this study is to classify the language mistakes in Decision Number 111/Pdt.P/2022/PN.Pgp and to examine the effects of such mistakes on the certainty of the law. In this work, we use a descriptive-analytical methodology informed by forensic linguistics to show how misspellings, improper grammar use, and poorly constructed sentences may lead to ambiguities that compromise the verdict. The results highlight the fact that fluency in standard English is crucial to the legitimacy of law enforcement, and not only for its aesthetic value.